Sexual harassment and sexual violence as predictors of risky sexual behavior among KIP-Kuliah Scholarship recipients: A cross-sectional study - Hetti Zuliani; Dina Amalia; Siti Naila Fauzia; Evi Rahmiyati; Khairiah Khairiah (ENLIGHTEN (Jurnal Bimbingan dan Konseling Islam), 2026)
Sexual harassment and sexual violence remain pervasive problems in higher education and are associated with adverse psychological, social, and health outcomes. However, evidence regarding how these distinct forms of victimization independently relate to risky sexual behavior among socioeconomically disadvantaged university students remains limited. This study examined the relationships between sexual harassment, sexual violence, and risky sexual behavior among recipients of the Kartu Indonesia Pintar Kuliah (KIP-Kuliah) scholarship at Universitas Syiah Kuala. A cross-sectional correlational design was employed involving 700 students selected through proportionate stratified random sampling. Data were collected using the SIKARES-M scale and analyzed using Pearson product moment correlation and multiple linear regression. The findings revealed that both sexual harassment and sexual violence were positively associated with risky sexual behavior, with sexual violence demonstrating a stronger influence than sexual harassment. Collectively, these experiences contributed substantially to explaining risky sexual behavior among KIP-Kuliah scholarship recipients. These findings support Revictimization Theory and Problem Behavior Theory and have important implications for the development of trauma-informed Guidance and Counseling services for KIP-Kuliah scholarship recipients and other socioeconomically disadvantaged university students.